Setting Up Decision-Making Tools toward a Quality-Oriented Participatory Maize Breeding Program - Alves, Mara L.; Brites, Cláudia; Paulo, Manuel; Carbas, Bruna; Belo, Maria; Mendes-Moreira, Pedro M. R.; Brites, Carla; Bronze, Maria do Rosário; Gunjača, Jerko; Šatović, Zlatko; Vaz Patto, Maria C. (Frontiers in Plant Science, 2017)
Previous studies have reported promising differences in the quality of kernels from farmers’ maize populations collected in a Portuguese region known to produce maize-based bread. However, several limitations have been identified in the previous characterizations of those populations, such as a limited set of quality traits accessed and a missing accurate agronomic performance evaluation. The objectives of this study were to perform a more detailed quality characterization of Portuguese farmers’ maize populations; to estimate their agronomic performance in a broader range of environments; and to integrate quality, agronomic, and molecular data in the setting up of decision-making tools for the establishment of a quality-oriented participatory maize breeding program. Sixteen farmers’ maize populations, together with 10 other maize populations chosen for comparison purposes, were multiplied in a common-garden experiment for quality evaluation. Flour obtained from each population was used to study kernel composition (protein, fat, fiber), flour’s pasting behavior, and bioactive compound levels (carotenoids, tocopherols, phenolic compounds). These maize populations were evaluated for grain yield and ear weight in nine locations across Portugal; the populations’ adaptability and stability were evaluated using additive main effects and multiplication interaction (AMMI) model analysis. The phenotypic characterization of each population was complemented with a molecular characterization, in which 30 individuals per population were genotyped with 20 microsatellites. Almost all farmers’ populations were clustered into the same quality-group characterized by high levels of protein and fiber, low levels of carotenoids, volatile aldehydes, α- and δ-tocopherols, and breakdown viscosity. Within this quality-group, variability on particular quality traits (color and some bioactive compounds) could still be found. Regarding the agronomic performance, farmers’ maize populations had low, but considerably stable, grain yields across the tested environments. As for their genetic diversity, each farmers’ population was genetically heterogeneous; nonetheless, all farmers’ populations were distinct from each other’s. In conclusion, and taking into consideration different quality improvement objectives, the integration of the data generated within this study allowed the outline and exploration of alternative directions for future breeding activities. As a consequence, more informed choices will optimize the use of the resources available and improve the efficiency of participatory breeding activities.